2023
DOI: 10.3389/fenvs.2023.1105077
|View full text |Cite
|
Sign up to set email alerts
|

Does ESG always improve corporate performance? Evidence from firm life cycle perspective

Abstract: In this study, drawing on firm life cycle theory, we focus on the corporate performance of Environmental, Social, and Governance (ESG) engagement via financial stress and consider the moderate effect of transparency, financial slack, and environmental uncertainty. The industry-year fixed effects panel regression analysis is executed based on the data including 11,742 firm-year observations for 1,486 Chinese A-share listed companies from 2010 to 2020. The results show that ESG performance can significantly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 81 publications
0
5
0
1
Order By: Relevance
“…The existing literature on ESG performance focuses on the economic consequences of ESG performance. Studies have found that improving ESG performance can enhance financial performance and firms' value [49][50][51][52], reduce accrued surplus management [55], alleviate financing constraints [56,57], improve customer stability [58], reduce corporate risk [62], etc. Fewer studies have focused on the factors influencing ESG performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on ESG performance focuses on the economic consequences of ESG performance. Studies have found that improving ESG performance can enhance financial performance and firms' value [49][50][51][52], reduce accrued surplus management [55], alleviate financing constraints [56,57], improve customer stability [58], reduce corporate risk [62], etc. Fewer studies have focused on the factors influencing ESG performance.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the economic consequences of ESG performance, considerable research has found that improving ESG performance can contribute to financial performance growth and enhance firm value [14,15,[49][50][51][52]. Profitability is one of the most critical indicators of a company and is related to shareholders' equity, long-term liabilities, provisions, deferred income within one year, total liabilities, working capital, and current assets [53].…”
Section: Esg Performancementioning
confidence: 99%
“…The life-cycle stages of "introduction," "growth," "maturity," "decline," and "shake-out" are identified and categorized in prior literature. The risks associated with a lending process such as default risk and credit risk may vary with different phases of the corporate life cycle (Gao et al, 2023). For instance, firms in the initial stages of their life cycle often face financial constraints, uncertainty regarding future cash flows, a shortage of liquid assets, and challenges in raising additional capital.…”
Section: Esg Cost Of Debt and Firm Life Cyclementioning
confidence: 99%
“…Neralla [36] , Ludwig and Sassen [22] , etc., measured from the perspectives of the board of directors' size, proportion of equity incentives, governance structure, and the quality of corporate internal control. Gao et al [37] argued that ESG can significantly improve firm performance at all life cycle stages, and the association between ESG and firm performance is more pronounced when the quality of corporate disclosure is high. Based on the research results of Chinese and foreign scholars, this study divides the internal corporate governance culture into the dimensions of shareholders' rights and interests, governance structure, letter approval quality, and governance risk.…”
Section: Dependent Variablementioning
confidence: 99%